A review on adapted models in technology acceptance - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (Human Resource Management Academic Research Society, 2022)
The 21st century of education has changed the education system, particularly in teaching pedagogy. Technology's incorporation into teaching and learning has become a worldwide phenomenon. This paper aims to review some models that were adapted and extended from the technology acceptance model (TAM). This paper focuses on models tested on practising and preservice educators’ acceptance of specific technology. This study uses meta-analysis in reviewing the pattern of adapted models in technology acceptance from 2003 until 2021. Most of the studies resulted in very significant results. The results also suggested that Technology Acceptance Model is a robust model in predicting educators’ behavioural intention in using new technology. Technology Acceptance Model can also be adapted and extended to indicate user acceptance in other fields. More extensive review in the adapted model in technology acceptance could be done since there are many other technology acceptance models such as Unified Theory of Technology Acceptance and Use of Technology